On-chip waste heat-driven absorption cooling system for sustainable data center environment: simulation - S. Manu; T. K. Chandrashekar (International Journal of Sustainable Engineering, 2018)
Development of waste heat-driven absorption-based cooling system is inspired for the need of removing high heat flux from the sustainable data centre environment. This paper presents a simulation study of single-stage Lithium Bromide–Water (LiBr–H2O) vapour absorption heat pump for chip cooling. In the present work, a complete thermodynamic analysis of the single-stage LiBr–H2O vapour absorption-based heat pump for chip cooling without a solution heat exchanger is performed and a user friendly graphical user interface (GUI) package including visual components is developed by using MATlab (2008b). The effect of chip heat flux on COP (Coefficient of Performance), flow rates and conductance is examined using the developed package. The model is verified using the data available in the literature which indicates that there is a greater reduction in the absorber load. The influence of chip heat flux on the performance and thermal loads of individual components are studied, and it is concluded that COP decreases from 0.7121 to 0.68924 with increase in chip heat flux.